(untitled) (Annals of Medical Research, 2021)
Aim: The aim of this study was to investigate the clinical features affecting on the recurrence of lung metastases of breast cancer. Materials and Methods: Data of 92 patients who had undergone pulmonary metastasectomy of breast cancer were examined in terms of recurrence, age, type of primary breast cancer, disease free interval (DFI), PET/CT findings, side of metastasectomy and number of resected lung metastases. Results: Solitary and unilateral pulmonary metastases presenting lower SUV following longer period of DFI were less involved in recurrence whereas invasive lobular and inflammatory carcinomas were more inclined to develop relapsing lung metastases. Age was not a risk factor for recurrence. Conclusion: Identifying high risk patients for recurrence contributes to prevention of repeating and excessive surgeries.